Novel spondyloepimetaphyseal dysplasia due to UFSP2 gene mutation. Issue 3 (12th January 2018) - Di Rocco, M.; Rusmini, M.; Caroli, F.; Madeo, A.; Bertamino, M.; Marre‐Brunenghi, G.; Ceccherini, I.
Abstract : Beukes hip dysplasia is an autosomal dominant disease which has to date been described only in a large South African family of Dutch origin. The patients presented with progressive epiphyseal dysplasia limited to femoral capital epiphysis and their height was not significantly reduced. A unique variant of the ubiquitin‐fold modifier 1 (Ufm1)‐specific peptidase 2 ( UFSP2 ) gene (c.868T>C) has been reported in all individuals from Beukes family with clinical and radiological diagnosis of Beukes hip dysplasia. Three individuals, propositus, mother, and grandmother, presented with short stature, joint pain, genu vara and a novel spondyloepimetaphyseal dysplasia involving epiphyses predominantly at hips, but also at knees, ankles, wrists and hands, associated with variable degrees of metaphysis and spine involvement. Exome sequencing allowed us to identify the heterozygous variant c.1277A>C of the UFSP2 gene, leading to the missense change p.D426A, in all 3 patients. This mutation is predicted as damaging and, similarly to the mutation originally described in the Beukes family (p. Y290H), directly affects one of the catalytic residues participating in the active site of the protein. This supports the novel notion that loss of catalytic UFSP2 activity, observed in association with different mutants and already experimentally proven in vitro, may have different clinical outcomes. Abstract : UFSP2 gene, reported in one family as cause of isolated hip dysplasia is responsible of a novel spondyloepimetaphyseal dysplasia.